The role of PAR-1 in regulating the polarised microtubule cytoskeleton in the Drosophila follicular epithelium. - Doerflinger, H.; Benton, R.; Shulman, J.M.; St. Johnston, D. (Development, 2003)
The PAR-1 kinase plays a conserved role in cell polarity in C. elegans, Drosophila and mammals. We have investigated the role of PAR-1 in epithelial polarity by generating null mutant clones in the Drosophila follicular epithelium. Large clones show defects in apicobasal membrane polarity, but small clones induced later in development usually have a normal membrane polarity. However, all cells that lack PAR-1 accumulate spectrin and F-actin laterally, and show a strong increase in the density of microtubules. This is consistent with the observation that the mammalian PAR-1 homologues, the MARKs, dramatically reduce the number of microtubules, when overexpressed in tissue culture cells. The MARKs have been proposed to destabilize microtubules by inhibiting the stabilizing activity of the Tau family of microtubule-associated proteins. This is not the case in Drosophila, however, as null mutations in the single tau family member in the genome have no effect on the microtubule organisation in the follicle cells. Furthermore, PAR-1 activity stabilises microtubules, as microtubules in mutant cells depolymerise much more rapidly after cold or colcemid treatments. Loss of PAR-1 also disrupts the basal localisation of the microtubule plus ends, which are mislocalised to the centre of mutant cells. Thus, Drosophila PAR-1 regulates the density, stability and apicobasal organisation of microtubules. Although the direct targets of PAR-1 are unknown, we suggest that it functions by regulating the plus ends, possibly by capping them at the basal cortex.